Fragile X syndrome: an overview of cause, characteristics, assessment and management. Issue 11 (November 2020) - Crawford, Hayley; Abbeduto, Leonard; Hall, Scott S.; Hardiman, Rebecca; Hessl, David; Roberts, Jane E.; Scerif, Gaia; Stanfield, Andrew C.; Turk, Jeremy; Oliver, Chris
Abstract: Fragile X syndrome (FXS) is the most common identifiable cause of inherited intellectual disability and autism spectrum conditions, and is associated with a range of physical, cognitive and behavioural characteristics. Alongside intellectual disability, heightened rates of autism spectrum disorder, anxiety disorders, attention-deficit-hyperactivity disorder, self-injury and aggression are reported. Timely identification of FXS as well as assessments of common co-morbid psychological conditions and underlying health problems are essential to ensure individuals with FXS receive appropriate support. This article provides an overview for clinicians of current literature on the cause of FXS as well as the key physical, cognitive, and behavioural characteristics with a focus on children and adolescents.